When the messenger is more important than the message: an experimental study of evidence use in francophone Africa - (:unkn) unknown (My University, 2022)
Background: Epistemic injustices are increasingly decried in global health. This study aims to investigate whether the source of knowledge influences the perception of that knowledge and the willingness to use it in francophone African health policy-making context. Methods: The study followed a randomized experimental design in which participants were randomly assigned to one of seven policy briefs that were designed with the same scientific content but with different organizations presented as authors. Each organization was representative of financial, scientific or moral authority. For each type of authority, two organizations were proposed: one North American or European, and the other African. Results: The initial models showed that there was no significant association between the type of authority or the location of the authoring organization and the two outcomes (perceived quality and reported instrumental use). Stratified analyses highlighted that policy briefs signed by the African donor organization (financial authority) were perceived to be of higher quality than policy briefs signed by the North American/European donor organization. For both perceived quality and reported instrumental use, these analyses found that policy briefs signed by the African university (scientific authority) were associated with lower scores than policy briefs signed by the North American/European university. Conclusions: The results confirm the significant influence of sources on perceived global health knowledge and the intersectionality of sources of influence. This analysis allows us to learn more about organizations in global health leadership, and to reflect on the implications for knowledge translation practices.
Keywords: African Research